A study on body image satisfaction, BMI status and dietary patterns among newly entrant girl students of Punjab Institute of Medical Sciences, Jalandhar - Sihag, Rubel; Joshi, Harshdeep (International Journal Of Community Medicine And Public Health, 2017)
Background: Body image is the perception that a person has of their physical self but more importantly the thoughts and feelings the person experiences as a result of that perception. Individuals who perceive their body negatively may have low self-esteem, low satisfaction in life and feeling of inferiority and pose themselves at a higher risk of depression. The aims and objectives of the study were to determine body image satisfaction among newly entrant girl students of Punjab Institute of Medical Sciences and to study dietary pattern of newly entrant girl students of Punjab Institute of Medical Sciences and estimate their BMI status. Methods: This was a cross - sectional study conducted among 80 newly entrant college girls of Punjab Institute of Medical Sciences. Between ages group of 17- 19 years attending first professional. The study strategy employed was via questionnaires and interviews. Results: In the current study majority of the girls i.e. 52% were dissatisfied with their body appearance. The striking finding was that 97% of participants who were dissatisfied belonged to urban area whereas 44.4% of the participants who were happy with their body image belonged to rural area and this difference was statistically significant (p<0.001). 89.7% girls despite having normal BMI were not satisfied with their body image where as 44.4% who had normal BMI were satisfied with their appearance. Conclusions: In the current study majority of the girls i.e. 52% were dissatisfied with their body appearance. Girls belonging to urban area had significantly higher body image dissatisfaction compared to girls from rural area.